Implementation of Reading, Write and Counting Learning Using the Montessori Method in Early Children - Ranudantha, Miranda; Fauziah, Puji Yanti (JPUD - Jurnal Pendidikan Usia Dini, 2025)
The research results show that the Montessori approach is effective in increasing the interest and ability of young children in learning Calistung. Children seem more independent and able to learn at their own pace. Teachers act as facilitators who guide children when needed, but most children carry out learning activities independently. The use of props such as sandpaper letters and number rods helps children develop a deeper understanding of letters and numbers. The Montessori method is an educational approach that emphasizes children’s independence in the learning process, and provides opportunities for young children to learn at their own pace and interests. In the context of learning to read, write and count for early childhood, this method integrates the use of teaching aids specifically designed to support children’s cognitive, motor and sensory development. The following is the implementation of Calistung learning using the Montessori method at the Radantha Montessori Pekanbaru tutoring, namely creating a structured environment, using interesting teaching aids, individual approaches and independent learning, learning through exploration and direct experience, holistic learning, and evaluating children’s progress. Montessori emphasized that each child has a different learning style, and therefore, Calistung learning is done individually. Children are given the freedom to choose teaching aids that are appropriate to their level of development, so that they can learn to read, write and count in the most effective way for them. The teacher acts as a facilitator who observes the child’s development and provides guidance if necessary, but does not force certain learning methods.